2018
DOI: 10.3389/fmicb.2018.01508
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Virulence-Associated Traits of Campylobacter jejuni Isolated From Poultry Food Chain and Humans With Diarrhea

Abstract: The objective of this study was to test the prevalence of virulence-associated markers and antimicrobial resistance in 624 C. jejuni isolated from poultry food chain, i. e., chicken feces (n = 160), poultry carcasses (n = 157), poultry meat (n = 152) and from humans (n = 155). All human strains were positive for 9 out of 13 putative virulence genes responsible for expression of pathogenic factors involved in different stages of the infection. The presence of all markers was also high in strains from chicken fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
60
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 60 publications
(126 reference statements)
29
60
2
Order By: Relevance
“…In the current study, 19% of the Campylobacter isolates from intestinal contents and 17.5% of the isolates from carcasses were positive for the wlaN gene. Similar rates were obtained previously by Wieczorek et al [49] in Poland at the level of 13.7% and 17.2% in isolates from chicken feces and carcasses, and by Guirado et al [18] in Spain at the level of 22% in chicken isolates. Additionally, in human origin Campylobacter isolates, the presence of the wlaN gene was estimated to be between 20% in Spain [18] and 17.4% in Poland [49].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the current study, 19% of the Campylobacter isolates from intestinal contents and 17.5% of the isolates from carcasses were positive for the wlaN gene. Similar rates were obtained previously by Wieczorek et al [49] in Poland at the level of 13.7% and 17.2% in isolates from chicken feces and carcasses, and by Guirado et al [18] in Spain at the level of 22% in chicken isolates. Additionally, in human origin Campylobacter isolates, the presence of the wlaN gene was estimated to be between 20% in Spain [18] and 17.4% in Poland [49].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, Kim et al [33], in studies on Campylobacter strains isolated from chicken and duck meat, detected a low rate of this marker, respectively, in 7.8% and 6.7% of the isolates. This marker was also identified sporadically in human clinical isolates, and the virB11 mutant can cause significantly less severe symptoms in vivo [48][49][50]. On the other hand, the rate of other markers involved in invasion, including the iam (invasion-associated marker), ciaB (Campylobacter invasive antigen B), and pldA (encoding a phospholipase A) genes, were commonly reported in previously conducted studies.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This gene along with cdtA and cdtC cytoxin gene has the ability to interfere with the division and differentiation of the intestinal crypt cells, ,thus has an important role in diarrhoea. This combination has been recorded with a prevalence of 96.6-97.6% in positive strains (50) which is in accordance with our study. It also suggests that the three genes( cdtA, cdtB and cdtC) should be included together in future studies for assessing toxic property.…”
Section: Prevalence Of Virulence Genessupporting
confidence: 92%
“…According to the paper, the reduction in Campylobacter population following plasma treatment fluctuated between 0.65 and 1.42 or 0.78 and 2.55 log CFU/cm 2 when air or argon was used as the working gas, respectively. Therefore, the authors suggested the nonthermal plasma as an effective disinfection technique for chicken fillet and chicken skin due to its effectiveness against C. jejuni (Rossow et al, 2018), which can be transmitted to human mainly through poultry products and lead to food infections (Wieczorek et al, 2018). Lee et al (2016) reported that DBD plasma treatment successfully decreased the number of total aerobic bacteria and pathogens in the vacuum packaged chicken breasts (Lee et al, 2016).…”
Section: 73mentioning
confidence: 99%